야간경관 평가에서의 아이트래킹 분석 적용 연구 - 강영은; Youngeun Kang; 김민태; Mintai Kim (한국조경학회지, 2015)
도시이미지 형성 및 지역 경제 활성화를 위해 국가 및 지자체별 야간경관계획 사업이 활발하게 추진되는 추세이지만, 현재까지 야간경관 관련 연구 부족 및 객관적인 평가 방법의 부재로 체계적인 야간경관계획이 이루어지지 않고 있다. 이에 본 연구에서는 피조사자들의 눈의 움직임 평가 및 설문조사를 통해 야간경관 특성을 분석하여, 향후 바람직한 야간경관계획에 시사점을 제공하고자 한다. 나아가 아이트래킹 기법(Eye-tracking method)이 경관 평가에 있어 객관적인 평가 방법이 될 수 있는지 검증하고자 하였다. 연구 대상지는 미국 버지니아 공과주립대 캠퍼스이며, 다양한 야간경관 이미지 중 전문가 평가를 통해 대표 야간경관을 선정하였다. 선정된 야간경관 이미지의 특성을 분석하기 위하여 사용된 변수는 선호도, 안전함(두려움), 선명도이며, 눈의 움직임 분석을 위한 변수는 고정 지속시간(fixation duration), 순간적 움직임 지속시간(saccade duration), 주사경로 길이(scan path length), 동공 크기(pupil size)이다. 분석 결과는 다음과 같다. 첫째, 다변량 분산분석(MANOVA)을 통하여 야간경관의 유형에 따라 선호도, 선명도, 안전함(두려움)의 차이가 통계적으로 유의하였으며, 상관관계 분석을 통해 선호도, 안전함, 선명도 사이에 정적인 영향관계가 있음을 도출하였다. 둘째, 야간경관의 유형에 따라 눈의 움직임 변수들(고정 지속시간, 지속시간, 주사경로 길이) 차이가 유의함을 파악하였으며, 상대적으로 오픈된 경관이 폐쇄된 경관보다 눈의 움직임 변수 수치가 낮은 것으로 조사되었다. 셋째, 눈 움직임 강도 지도(Heat map) 비교 분석에서는 피조사자들이 무의식적으로 응시한 강도 지도 결과와 선호되는 구역 및 선명하게 보이는 구역 응시를 지시했던 강도 지도 결과가 유사하게 나타나는 결과를 확인하였다. 이는 사람들이 무의식적으로 야간경관을 응시할 때, 다른 구역에 비하여 주로 선호하고, 선명하게 보이는 구역을 강하게 응시한다는것을 의미한다. 종합해볼 때, 본 연구에서는 야간경관의 유형에 따라 전체적인 선호도, 선명도, 안전함(두려움) 등의 지각하는 특성 및 눈의 움직임 차이를 검증할 수 있었으며, 나아가 야간경관 구역별 강하게 응시하는 구역과 해당 구역이 의미하는 특성을 파악할 수 있었다. 본 연구 결과는 경관 평가에 있어 아이트래킹 기법 적용하여 환경별 유의미한 차이를 입증했다는데에 의미하는 바가 크며, 향후 경관 평가에 시사점 제시 및 야간경관의 이용 만족도 향상을 위한 야간경관계획 시전략적으로 참고할 수 있을 것이다. There’s a trend towards vitalization of nightscape planning businesses nationally and locally as well for city image making and activation of regional economy, but there is still no systematic nightscape planning going on for lack of relevant researches and objective evaluations. This study aims to suggest the guideline for nightscape planning by conducting an eye tracking experiment and survey for recognizing the characteristics of a nightscape. Furthermore, the authors intended to verify the eye-tracking method as a tool for landscape evaluation. The research site was restricted in the campus of Virginia Tech, VA, and those were selected by experts’ survey among various types of nightscape images. The variables for analyzing the characteristics of nightscape images selected were ‘preference’, ‘safety(fear)’ and ‘clearness’. ‘Fixation duration’, ‘saccade duration’, ‘scan path length’, and ‘pupil size’ were selected as the eye movement measurements. The results of this study are as follows: The first outcome found was that there were significant differences among the characteristics(preference, safety and clearness) of a nightscape by MANOVA, and these variables were correlated positively by Pearson``s correlation. Secondly, there were differences on fixation duration, saccade duration and scan path depending on the nightscape setting statistically. Also, the eye tracking measurement in an open setting was recorded lower than enclosed settings. In the result of a heat map, we found the meaning of the fixated areas on both viewing without intention and viewing intentionally. It turned out that the fixated areas were consistent with the areas the subjects felt preferred and clarity in all of the nightscape images, which means people usually focus on what they prefer and see clearly in a certain nightscape. Based on this result and previous studies, the authors could make a conclusion that eye tracking method can apply to evaluate nightscape settings in terms of analyzing the whole characteristics and finding specific points for the detailed analysis as well. Therefore, these results can contribute by suggesting nightscape planning, implication of the landscape evaluation, and implication of the eye tracking study.